Kebudayaan Lokal Pacitan: Nilai Pendididkan Islam dalam Tradisi Ceprotan di Desa Sekar Kecamatan Donorojo - Prahastiwi, Eka Danik; Aorta, Dian Tias; Irawan, Agus (Lembaga Yasin AlSys, 2023)
This article is the result of research that aims to determine the value of Islamic education in an effort to preserve, one of the customs in Pacitan, East Java before Donorojo Regency, Pacitan, East Java, in the traditional ceprotan ceremony. Data collection techniques used in this study were in-depth interviews, direct observation, notes and archived documents. The data analysis technique in this study applies an interactive model, both in data collection, data reduction, data presentation, and drawing conclusions. The results showed that the community's understanding of the tradition (ceprotan) in Sekar village was relatively normal, with high awareness and understanding of their beliefs or the community. The community's understanding of the clean village tradition (ceprotan), teachings passed down from ancestors in order to be grateful for the gift of God Almighty.